Organocatalytic enantioselective Mannich reaction of isoxazol-5(4H)-ones to isatin-derived ketimines. Issue 43 (14th October 2022) - Torán, Ricardo; Puchán, Dario; Sanz-Marco, Amparo; Vila, Carlos; Pedro, José R.; Blay, Gonzalo
Abstract : An efficient organocatalytic asymmetric Mannich reaction between isoxazol-5(4 H )-ones and isatin-derived ketimines has been developed. Abstract : An efficient organocatalytic asymmetric Mannich reaction between isoxazol-5(4 H )-ones and isatin-derived ketimines has been developed. A bifunctional squaramide/Brønsted base organocatalyst catalyzed the enantioselective Mannich addition to afford chiral 3-aminooxindoles bearing a tetrasubstituted stereocenter at C3 decorated with an isoxazole moiety in good yields and with excellent enantioselectivities. Additionally, several synthetic transformations were described showing the versatility of the prepared compounds.